The Transition Effect of Korea’s Space Development - Jong-bum Kim (International Journal of Advanced Culture Technology(IJACT), 2018)
In the 1990s, South Korea recently launched Space Development and is pushing for a step toward Space. In the Space Launch Vehicle field, the development of Practical satellite type Launch Vehicle (Korea Space Launch Vehicle II) has progressed to the stage of proprietary development, and in the field of Satellite development, they also have a great deal of competitiveness. This study will be a shortcut to rediscovering our potential and looking for breakthroughs by reviewing and re-examining the effects of past Space development.